Nucleotide sequence characterization of the non-coding regions in the genomic DNA of the ribosomal protein gene,RPL41, from human nasopharyngeal-derived cell line - Nurulain, binti Marikan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Nasopharyngeal carcinoma (NPC) is found to be associated with mutations occurring in the nasopharynx tissue and the deregulated expression of the ribosomal protein (R'P) genes. Recent study shows the role of RPL41 as a tumor suppressor gene in the malignant transformation in cancer cells. Genes with down-regulation of the RPL41 has abnormal mitosis process and cytokinesis failure which contributes to gene instabiHty and subsequent tumor formation. Hence, it is essential to study the association between RPL41 and NPC and the non-coding regions of the RPL41 is chosen in this study as these regions plays essential roles in gene expression, regulation, apoptosis and possibilities of disease such as cancers. Non-coding regions of RPL41 were isolated from normal cell line (NP69) and malignant cell lines (HONE and HK-I) by using pre-designed primers. The desired length of gene product was directly purified and sent to Ist Base Laboratories for sequencing. However, the sequence data obtained for the malignant cell lines was not fully sequenced, thus arresting the nucleotide comparison process. Thus, no mutational analysis accomplished for nasopharyngeal carcinoma.